2017
DOI: 10.3892/ol.2017.6755
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant EPHB4 gene methylation and childhood acute lymphoblastic leukemia

Abstract: The present study aimed to investigate the association between aberrant DNA methylation of the promoter region of the ephrin type-B receptor 4 (EPHB4) gene and the development of childhood acute lymphoblastic leukemia (ALL). Bisulfite sequencing polymerase chain reaction (BSP) was performed to determine the methylation density of cytosine-guanine pair islands in the promoter region of EPHB4, in bone marrow samples from 40 children with ALL. The mRNA and protein expression levels of EPHB4 were detected using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Specifically, the observation that a high expression of EPHA2 in neuroblastoma [103], EPHB1 in glioma [79], EPHB6, ephrin-B2, and ephrin-B3 in neuroblastoma [101] correlates with a better prognosis is in line with a tumor-suppressive role of these EPHs. EFNB1 has been identified among downregulated DEGs in children diagnosed with AML [134], while bone marrow samples from pediatric AML patients are characterized by EPHB1 promoter hypermethylation with subsequent decreased EPHB1 expression [136], while analogously for the case of pediatric ALL, the observed increased EPHB4 methylation resulting in decreased EPHB4 expression may contribute to leukemia development and progression [131]. Interestingly, as it is observed for the case of EPHB4, the same EPH can exert either a pro-tumorigenic (i.e., in neuroblastoma and rhabdomyosarcoma [106,120]) or anti-tumorigenic function (i.e., in ALL [131]) depending on the type of neoplasm it is expressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the observation that a high expression of EPHA2 in neuroblastoma [103], EPHB1 in glioma [79], EPHB6, ephrin-B2, and ephrin-B3 in neuroblastoma [101] correlates with a better prognosis is in line with a tumor-suppressive role of these EPHs. EFNB1 has been identified among downregulated DEGs in children diagnosed with AML [134], while bone marrow samples from pediatric AML patients are characterized by EPHB1 promoter hypermethylation with subsequent decreased EPHB1 expression [136], while analogously for the case of pediatric ALL, the observed increased EPHB4 methylation resulting in decreased EPHB4 expression may contribute to leukemia development and progression [131]. Interestingly, as it is observed for the case of EPHB4, the same EPH can exert either a pro-tumorigenic (i.e., in neuroblastoma and rhabdomyosarcoma [106,120]) or anti-tumorigenic function (i.e., in ALL [131]) depending on the type of neoplasm it is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…EFNB1 has been identified among downregulated DEGs in children diagnosed with AML [134], while bone marrow samples from pediatric AML patients are characterized by EPHB1 promoter hypermethylation with subsequent decreased EPHB1 expression [136], while analogously for the case of pediatric ALL, the observed increased EPHB4 methylation resulting in decreased EPHB4 expression may contribute to leukemia development and progression [131]. Interestingly, as it is observed for the case of EPHB4, the same EPH can exert either a pro-tumorigenic (i.e., in neuroblastoma and rhabdomyosarcoma [106,120]) or anti-tumorigenic function (i.e., in ALL [131]) depending on the type of neoplasm it is expressed. We should note, though, that for certain EPH/ephrin members, such as EPHB1 in medulloblastoma [69] and EPHB2 in ependymoma [95], the reported variable levels of expression render the characterization of their role in tumorigenesis ambiguous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association with an unfavorable prognosis has also been observed. Therefore, the authors proposed that the EPHB4 gene may function as a potential tumor suppressor in childhood ALL [147]. Another study by Kuang et al identified hypermethylation of multiple EPH and ephrin genes (i.e., EPHA2, -A4, -A5, -A6, -A7, -A10, EPHB1, -B2, -B3, -B4, EFNA1, -A3, -A5, and EFNB1 and -B2) in leukemia cell lines and primary ALL BM samples.…”
Section: Leukemias Of Lymphoid Originmentioning
confidence: 99%
“…Sixty-five records were identified about the relationship of GSTT1 polymorphisms and children acute leukemia risk. According to the selection criteria, 7 studies [10][11][12][13][14][15][16] were suitable and the remaining was removed. The publication year of all included articles ranged from 2003 to 2013.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%